ROBOTIC SURGERY FOR GIANT PRESACRAL DUMBBELL-SHAPE SCHWANNOMA - Farid Yudoyono; Muhammad Zafrullah Arifin; Rully Hanafi Dahlan; Sevline Estethia Ompusunggu; Shin Dong Ah; Yi Seong; Yoon Do Heum; Kim Keung Nyun (International Journal of Integrated Health Sciences, 2015)
Objective: To demonstrate the feasibility of using da Vinci robotic surgical system to perform spinal surgery.